Integrasi Kesehatan Lingkungan dalam Aktivitas Kebugaran sebagai Upaya Peningkatan Longevity - Hammado, Nurussyariah; Ichsania, Nurul; Hammado, Nururrahmah (Program Studi Manajemen FEB UNM, 2026)
Environmental health plays a crucial role in supporting performance and longevity among athletes and fitness communities; however, its implementation remains suboptimal. This community service program aimed to improve awareness and healthy behavior through a participatory, community-based approach. A total of 25 participants were involved in an intervention integrating experiential learning, nudge-based strategies, and social norm reinforcement. The program began with environmental mapping of training areas, followed by interactive, practice-based education and behavior reinforcement through environmental modifications and community change agents. The intervention focused on equipment hygiene, air quality awareness, and hydration management. Evaluation was conducted qualitatively through observation and group reflection without pre–post testing. The results indicated improved understanding and behavioral changes, including consistent equipment cleaning and increased environmental awareness. Academically, these findings support the effectiveness of experience-based and environment-focused interventions in promoting sustainable health behavior. The program contributes to creating a healthier training environment and supports long-term well-being and longevity among physically active individuals.